Beyond the Niche Hypothesis. Property, Marrriage, and the Onset of Familial Reproduction in Rural Northwest Germany, 1820−1866 - Georg Fertig (Historical Life Course Studies)
The study applies event history analysis to nominative data of three contrasting localities to explore the relationship between property transmission and family formation. This allows testing several hypotheses concerning demographic regulation and family dynamics in preindustrial Europe, including but not limited to the niche hypothesis. The analysis finds evidence for four mechanisms of family formation. Firstly, the death of one or both parents promoted marriage of their children. For farmholders, niche inheritance was an important contribution; but parental death also leads to an increase of nuptiality among those who did not own landed property. Beyond ownership, the importance of familial labour roles, particularly of older and younger women, can explain this observation. Second, marriages resulted from the accumulation of an appropriate marriage fund, as indicated by the results that purchases of land and favorable relative prices contributed to the conclusion of marriages. Third, there was an independent role for family dynamics in the sense that property transmission to one child promoted marriage of siblings. The fourth mechanism relates to autonomous family formation through marriages resulting from sexual encounters (indicated by premarital pregnancy). The relative weight of these four mechanisms is remarkably stable across social class and ecotype.